From campus to career - Mercy Etakpobunor Agbamu (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
Career choices are important part of transitioning to the job market especially for graduating university students. It involves selecting a specific occupation or field based on their education, interests, values, and goals. The current study aims to investigate the impact of psycho-social values and socioeconomic motivations on career choices among 1200 fresh graduates from Delta State University. It explores how students’ identity formation, influenced by cultural assimilation and social interactions, informs their professional decisions as they transit into the workforce. By using a cross-sectional survey design, data were collected through structured questionnaires from a sample of 300 graduating students who were selected through a stratified random sampling method across one hundred undergraduate university programmes. Pearson correlation and multiple regression analyses were performed using SPSS Version 23 to examine the relationships between psycho-social values, socioeconomic motivations, and career choices. The analysis revealed that both psycho-social values and socioeconomic motivations significantly influence career choices. However, psycho-social values had a moderate to strong correlation with career choices (r=0.56, p<0.01), while socioeconomic motivations demonstrated a stronger correlation (r=0.62, p<0.01). The regression model explained 48% of the variance in career choices, with socioeconomic motivations showing a higher impact (β=0.50, p<0.0001) compared to psycho-social values (β=0.45, p<0.0001). The findings indicate that while internalized psycho-social values play a notable role in shaping career aspirations, socioeconomic factors exert a more substantial influence.